The effect of buckling in FRP members - Ibrahim, Mohd Halim Irwan (2005)
The field of composite materials is both old and new. It is only since the early 1960s have engineers and scientists exploited seriously the vast potential of fabricated fibrous composite materials. Development of new composites and new applications of composites is now accelerating. This project is a study of how the critical load changed if we varying the length of strut. Besides that, we need to design the test rig that hold column during the buckling test with using fixed-fixed as the boundary condition. Comparison between the buckling test method and theoretical from resin burn-off test data will be analysed and determine the suitable length that valid through compression or buckling. Any error occurs between theoretical and experimental will be minimize by modify the original equation of Euler Equation. Here, the aspects that we will see is the factor which contribute to the effect of buckling whether the length, geometry, Young's modulus or the volume fraction of fibres ,etc.